The Power Of Politic and Lobbying Parties in the Australian Accounting Regulation Reform Program - Suwaldiman Suwaldiman (Jurnal Akuntansi dan Auditing Indonesia, 2004)
This paper argues that Australian accounting regulations seem to be close to the government or political approach in its setting process. CLERP (Corporate Law Economic Reform Program) proposed by government can be viewed as changes made by Federal Government in the structure of setting accounting standards that show a substantial shift in power from the two professional accounting bodies; ICAA (The Institute of Certified Accountants in Australia) and ASCPA (Australian Society of Certified Practising Accountants) to the government. The CLERP rules accounting standard setting and companies must comply with proliferation of regulations. The government involvement in setting accounting standards as stated in the CLERP is to reach a high quality of accounting standards, to lead the lower costs of capital and to protect public interest from corporate collapse. However those efforts are aggravated by private interest lobbying that is more powerful and close to political process. Potential winners or losers will use lobbying to influence the authority so that the outcomes of setting accounting standards will protect their private interest. Finally the force of law of accounting standards will increase companies’ distress in facing the proliferation of regulations that must be complied.Keywords:     Australian accounting regulations, politic parties, lobbying parties, accounting standards